2017
DOI: 10.3171/2016.12.spine16914
|View full text |Cite
|
Sign up to set email alerts
|

Does the mesodermal derangement in Chiari Type I malformation extend to the cervical spine? Evidence from an analytical morphometric study on cervical paraspinal muscles

Abstract: OBJECTIVEThe mesodermal derangement in Chiari Type I malformation (CMI) has been postulated to encompass the cervical spine. The objectives of this study were to assess the cross-sectional areas (CSAs) of cervical paraspinal muscles (PSMs) in patients with CMI without syringomyelia, compare them with those in non-CMI subjects, and evaluate their correlations with various factors.METHODSIn this retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…Noting a recent Epub prior to print study that reports greater cervical spine taper ratios in Chiari I than in controls, we performed a regression analysis of taper ratios and tonsil herniation in our data. 12 We found significantly steeper C1–C4 and C1–C7 taper ratios in our 23 patients with presyrinx, but no significant correlation of tonsil herniation and lower cervical spine tapering (C4–C7) in our patients.…”
Section: Discussioncontrasting
confidence: 52%
“…Noting a recent Epub prior to print study that reports greater cervical spine taper ratios in Chiari I than in controls, we performed a regression analysis of taper ratios and tonsil herniation in our data. 12 We found significantly steeper C1–C4 and C1–C7 taper ratios in our 23 patients with presyrinx, but no significant correlation of tonsil herniation and lower cervical spine tapering (C4–C7) in our patients.…”
Section: Discussioncontrasting
confidence: 52%
“…In addition, the sectional area of the RCDmi myofibers in the BLM group was found to be larger and these myofibers appeared to be more tightly packed than those observed in the other groups. This suggests that the RCDmi might be accompanied by compensatory hypertrophy (Thakar et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed the same tendency that the CSA of Trap, SSC, LS, SCM, and LCap & LC were smaller in BI patients. Moreover, we supposed that the FCSA/CSA ratio was more meaningful than muscle size, but it was absent in the study of Thakar et al [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the muscle morphology in BI patients had been rarely reported so far. Thakar et al [ 18 ] investigated the cervical paraspinal muscles in 25 patients with Chiari I malformation, a common complication of BI, and found that the dimension of cervical paraspinal muscles including superficial, deep flexor and extensor were smaller than that of the control group. The authors calibrated the muscle CSA with vertebra body CSA to eliminate biases in body size so that we could not directly compare our muscle CAS results with theirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation